Evaluation of patient satisfaction following the grafting of autologous fat tissue obtained by VASER-assisted liposuction (Annals of Medical Research, 2023)
Aim: Autologous fat transplantation, also known as fat grafting or fat injection, is an increasingly popular technique in reconstructive surgery with minimal complications and low morbidity rates. The aim of this study is to evaluate the satisfaction of patients after the injection of autologous adipose tissue obtained by the Vibration Amplification of Sound Energy at Resonance (VASER)-assisted lipoplasty method due to aesthetic concerns or deformity.Materials and Methods: The study includes 20 patients who underwent VASER-liposuction-guided autologous fat injection between 2014 and 2021 in a single center. Patients were invited for follow-up approximately three years after the surgical intervention, and patient satisfaction and complications were evaluated with a semi-structured questionnaire.Results: Patient and surgeon satisfaction received the highest score at discharge. Sensory changes and tissue stiffening were found to be the most common complications. Overall satisfaction and scar healing were identified as the parameters with the highest score.Conclusion: VASER- assisted liposuction and autologous fat transplantation is a technique associated with high patient satisfaction and minimal complications. The method is an ideal technique for whole body contouring and facial operations.
Keywords: VASER; Liposuction; Autologous fat tissue; Patient satisfaction